The Perception of UTAR Ed & El Undergraduates on the Impacts of Facebook in Enhancing their ESL Writing Skills - Kristina Francis; Sumita Padmanathan (Jurnal Pendidikan Indonesia, 2023)
The advancement of information, communications, and technology (ICT) has made social media an indispensable tool for language learning, especially second language learning. This study aims to analyze the perception of undergraduates on the positive impacts of social media particularly Facebook by utilizing Facebook in improving ESL writing skills. Using TAM as the theoretical lens, this quantitative-method research involved questionnaire survey. The sample consisted of 50 undergraduates. The questionnaires were distributed in a Google form to the 30 English Education undergraduates. By doing this, the researcher was able to gather and analyse their perception on the impacts of Facebook in enhancing ESL writing skills. Results of the analysis showed that the perception of participants towards the usage of Facebook that significantly influenced their ESL writing skills. The positive impacts of Facebook concerning ESL writing skills were also depicted via the statistical analysis. The findings provide an insight to stakeholders in suggesting ways to encourage the use of Facebook in language learning specifically writing skills. Similar research can be done in the future by involving a larger number of participants from different private higher education institutions.